Peningkatan Akuntabilitas dan Transparansi Melalui Pelatihan Keuangan Digital di Madrasah Diniyah Ar-Razaq - Misbahul Arifin; Abdul Majid; Ramzatul Widad Rizqiyani; Layli Rohmatillah; Ulfa Qomariatul Jannah (Transformative Service Journal, 2025)
Accountable and transparent financial management is crucial for the sustainability of institutions like Madrasah Diniyah, which often face hurdles in adopting digital systems. This Community Service (PkM) activity focuses on improving the accountability and transparency of financial management at Madrasah Diniyah Ar-Razaq through digital application-based training for treasurers. The research methods involved initial needs identification, development of a hands-on training curriculum using simple spreadsheet-based financial applications, logistical preparation, and the formation of an implementation team. Program implementation included socialization, inclusive training, intensive post-training mentoring, and strengthening the madrasah's digital resources. Monitoring results showed a significant improvement in the treasurers' ability to manage digital transactions, while impact evaluation indicated enhanced record-keeping accuracy and ease of financial reporting, which in turn boosted stakeholder trust. The implication of this community service program is the creation of a better digital ecosystem within the madrasah, although sustainability and internal support require continuous strengthening, with recommendations for internal policies mandating application usage and ongoing support.